The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1111/j.1550-7408.1979.tb02726.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Macronuclear DNA Content in Tetrahymena thermophila*†

Abstract: Synopsis. Unequal macronuclear division in Tetrahymena thermophila introduces variance into G1 macronuclei; unless eliminated such variance would result in continuous variation in DNA content. Analysis of G1 and G2 macronuclear variances reveals that the added variance is eliminated by action on the extremes of macronuclear DNA content. In this model (Model II), macronuclei with small amounts of DNA have an additional complete S phase, while those with large amounts of DNA skip S. From available data, chromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Tetrahymena's amitotic (AM) MAC is characterized by a G1-S-G2-AM cell division cycle, which roughly coincides with the regular G1-S-G2-M pattern seen in mitosis (Figure 6E; Flickinger, 1965;Woodard et al, 1972;Doerder, 1979;Cole and Sugai, 2012). The MIC undergoes more conventional mitosis, though with no apparent G1 interval.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Tetrahymena's amitotic (AM) MAC is characterized by a G1-S-G2-AM cell division cycle, which roughly coincides with the regular G1-S-G2-M pattern seen in mitosis (Figure 6E; Flickinger, 1965;Woodard et al, 1972;Doerder, 1979;Cole and Sugai, 2012). The MIC undergoes more conventional mitosis, though with no apparent G1 interval.…”
Section: Discussionmentioning
confidence: 59%
“…The MIC undergoes more conventional mitosis, though with no apparent G1 interval. MIC S phase and mitosis are temporally out of phase with the MAC nuclear cycle (Figure 6E; Flickinger, 1965;Woodard et al, 1972;Doerder, 1979). The highly synchronized cell populations we can obtain by CCE will allow us to address important questions in Tetrahymena biology.…”
Section: Discussionmentioning
confidence: 93%
“…Analysis of variances of DNA content in pre‐replication vs. post‐replication cells showed that in Paramecium the coefficient of variation is halved during the replication process (Berger and Schmidt 1978). In contrast, macronuclear DNA content in Tetrahymena is doubled and the coefficient of variation remains constant (Doerder 1979). We postulated that all Paramecium cells were making the same amount of DNA.…”
Section: Regulation Of Macronuclear Dna Contentmentioning
confidence: 99%
“…This system for regulation of DNA content is very different from that in Tetrahymena in which the prereplication DNA content (i.e. genome copy number or gene dosage) determines whether 0, 1 or 2 complete rounds of DNA replication occur within the cell cycle (Cleffmann 1968, 1975; Cleffmann, Reuther, and Seyfert 1979; Doerder 1979; Doerder and DeBault 1978).…”
Section: Regulation Of Macronuclear Dna Contentmentioning
confidence: 99%